EXPLORATION OF SELF-REGULATION IN DEALING WITH PEER PRESSURE AMONG STUDENTS AT MA MADINATUSSALAM - Siti Khairani Amnur; Salamiah Sari Dewi; Suryani Hardjo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research is an in-depth exploration of students' struggles in confronting peer pressure within the school environment. These various pressures, such as a consumerist lifestyle, cheating behavior, and mild bullying, are not just social issues, but a serious test of students' integrity and authentic identity. The goal of this study is to document their real-life experiences and uncover the self-regulation strategies that enable them to survive, and even thrive, amidst these challenges. Through an interpretive phenomenological approach, this qualitative research deeply delves into the students' experiences. Findings indicate that amidst the onslaught of peer pressure, students face a major dilemma: between the intense desire to be accepted by the group and the drive to maintain their true selves. The path toward self-reliance is not easy; it requires the integration of mutually reinforcing strategies. The participants successfully navigated this internal conflict by utilizing strategies for reinforcing self-values and principles as a moral compass, motivational strategies grounded in future aspirations, assertive communication as a shield, and time and stress management as tools for staying focused. This study highlights that merely having high aspirations is insufficient to guarantee success. Without a strong foundation of principles, these aspirations can be fragile and easily swept away by the current. Conversely, principles without strong motivational drive risk trapping an individual in stagnation. This finding serves as a valuable reminder to us all: that the courage to be different and the self-awareness to manage oneself are the keys to unlocking full potential. Through this research, it is hoped that educators, parents, and students themselves will be inspired to build